Productivity and Nutritional Quality of Four Elephant Grass (Pennisetum purpureum) Cultivars under Biochar and Organic Fertilizer Applications at the Third Harvest on Post-Nickel Mining Soil - Widhi Kurniawan; Chusnul Hanim; Nafiatul Umami (Buletin Peternakan, 2026)
Nickel mining activities degrade soil quality, necessitating improvement. Post-mining reclamation requires strategic efforts with soil amendments and adaptive plants. Superior grass not only serves as a forage source but also improves soil quality and supports ecosystem stability on degraded land. This study aims to evaluate the effect of biochar and organic fertilizer (OF) (soil amendment agent, SAA) on the productivity and forage quality of the third harvest of four elephant grass cultivars on nickel post-mining land. The study used a factorial design consisting of: Control [-] , Control [+], SAA1 = 5 tons/ha biochar + 20 tons/ha OF, and SAA2 = 10 tons/ha biochar + 20 tons/ha OF. Four elephant grass cultivars were utilized, namely: P. purpureum, P. purpureum cv. GU; P. purpureum cv. Mott, and P. purpureum cv. Thailand. The results showed that SAA2 treatment significantly increased dry matter (DM) production and forage digestibility compared to other treatments. P. purpureum cv. The GU produces the highest DM yield (8,885.07 kg/ha) with good nutritional quality and the highest digestibility—the combination of SAA2 × P. purpureum cv. The GU provides optimum DM productivity (12,094.80 kg/ha) and is recommended as a strategic alternative for providing forage while supporting post-nickel mining land reclamation.